RETRACTED: Extracellular Vesicles Carry lncRNA SNHG16 to Promote Metastasis of Breast Cancer Cells via the miR-892b/PPAPDC1A Axis - Xia, Wenfei; Liu, Yun; Cheng, Teng; Xu, Tao; Dong, Menglu; Hu, Xiaopeng (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer (BC) represents the most commonly diagnosed malignancy among women. Long non-coding RNAs (lncRNAs) can be transferred by extracellular vesicles (EVs) to participate in BC progression. This study demonstrated that SNHG16 expression was significantly increased in BC tissues and cells. Overexpression of SNHG16 promoted the migration, invasion, and epithelial–mesenchymal transition (EMT) of BC cells. SNHG16 was carried by EVs. Bioinformatics analysis predicted that SNHG16 regulated PPAPDC1A expression by sponging miR-892b, which was confirmed by RNA-fluorescence in situ hybridization (FISH), RT-qPCR, dual-luciferase gene reporter assay, and RNA immunoprecipitation (RIP). MDA-MB-157 and HS578T cells were transfected with pcDNA3.1-SNHG16, miR-892b-mimic, or si-PPAPDC1A for functional rescue experiments in vitro, and the cells were treated with MDA-MB-231 cell-derived EVs. The results confirmed that enhanced miR-892b expression partially eliminated the increase of migration, invasion, and EMT of BC cells mediated by SNHG16 or EVs. The lung metastasis model in nude mice was established by injecting HS578T cells via tail vein. The results showed that si-SNHG16 reduced the metastatic nodules and decreased the vimentin expression. In conclusion, EVs derived from BC cells transferred SNHG16 via the miR-892b/PPAPDC1A axis, thus promoting EMT, migration, and invasion of BC.